PERGESERAN TATA CARA PERKAWINAN MASYARAKAT BATAK TOBA DI DESA SAWIT PERMAI KECAMATAN DAYUN KABUPATEN SIAK - ', Feronika; ', Isjoni; ', Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The development of the times affects the occurrence of a change in any part of traditional wedding ceremony Toba Batak society. Change is meant to add or subtract certain obligations in the marriage ceremony. Conduct marriage ceremonies Batak Toba first implemented in time and the process is quite long, now shortened to the term customary upcaraulaon realize (the party which was completed during the day). The stages in a traditional wedding ceremony in the form of ulaonsadarai is that began with marhusip, martumpol, marhatasinamot, party rally which directly followed by the show paulakune and maningkir stairs. In general, the stages were shortened this custom event when viewed in terms of time is very beneficial because it gives people an opportunity to pursue other needs. However, if viewed in terms of education and knowledge, it is detrimental to the younger generation now because with dipersingkatnya stages of marriage caused the younger generation no longer know how the stages of the marriage in accordance with the original cultural values ​​Batak Toba.The purpose ofthis study was tofind out howthe proceduremarriageBatakTobacommunityinthe area of origin, to knowhow toshiftthe execution ofcustomarymarriagesin thecommunityin the village ofBatakTobaSawit Permai subdistrictDayunSiak, knowingthe impactothe shift inthe implementation of customary marriage inBatakTobaSawit Permai inthe DistrictDayunSiak.The methodusedin this studyis aqualitativeapproachmethod. The research locationis village Sawit Permai subdistrictDayunSiak. When the studyas from thestartuntil theproposalseminarthesis examination. Data collection techniqueswithinterviews and observations.These results indicatethat theshiftoccurredMarriageProceduresinTobaBatakSociety village SawitPermaiinthe DistrictDayunSiakimpactsboth positive andnegative effects. Keywords: Shift, Marriage, Batak Toba